PENGARUH KOMPETENSI KEWIRAUSAHAAN TERHADAP KINERJA USAHA UMKM KOPI: SEBUAH TINJAUAN TEORITIS DAN EMPIRIS - Suryana, Anggita Tresliyana; Burhanuddin, Burhanuddin (Jurnal AGRISEP, 2021)
Coffee MSMEs in Indonesia is growing with an increase in domestic coffee consumption in Indonesia. However, coffee MSME also experiences various business development problems due to entrepreneurial competencies. Further studies are needed to understand what competencies affect coffee MSME performance, so that they can develop entrepreneurial development strategies more precisely. The result of this study provides finding indicated an effect of entrepreneurial competence on the business performance of coffee MSMEs in Indonesia. In general, the variables that influence coffee UMKM entrepreneurial competencies are conceptual abilities, skills and individual characteristics. To develop the business performance of Indonesian coffee MSMEs, strategy need to be carried out is to increase the capability of coffee MSME entrepreneurs in both technical and management fields.